Modifikasi Rencana Pelaksanaan Pembelajaran (RPP) Menghapal Hadist di Madrasah Ibtidaiyah - Nurul Malikah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2018)
Research to study the development of learning planning conducted by teachers in hadith study in madrasah. All teachers are required to have a learning planthat serves as a teaching guideline to achieve the specified target. The Learning Implementation Planning that has been planned by the teacher is aformat that has been determined by the center so that teachers follow the preparation of The Learning Implementation Planning. This article discussesthe development of The Learning Implementation Planning preparation by teachers as a guidance for teaching memorizing of hadiths in religious schools.The discussion is conducted on the learning process activities that allocate the right time in each stage of the activity from the introduction, core and closing.The results obtained in the research is the format of RPP in learning memorizing the hadith in religious schools. The new format becomes morestructured guidance with clear time allocations according to the time set. The time set leads the learning process sequence in accordance with the activitiesundertaken by students and teachers in memorize of hadith. This can make it easier for the teacher to invite the students to memorize the hadith because theword arranged in order is used to match the time of the memorization, the students’ activities when memorizing and the teacher’s activities when directing the memorization process.